2023
DOI: 10.1093/cid/ciad027
|View full text |Cite
|
Sign up to set email alerts
|

Disease Transmission by Patients With Subclinical Tuberculosis

Abstract: Background Subclinical tuberculosis has been increasingly recognized as a separate state in the spectrum of the disease. However, evidence on the transmissibility of subclinical tuberculosis is still inconclusive. Methods We reanalysed the data from the 2007 combined tuberculosis prevalence and tuberculin surveys in Vietnam. Poisson regression with robust standard errors was conducted to assess the effect of clinical presenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Through this lens, data from extensive community TB screening efforts utilizing sputum-GeneXpert – which have identified large numbers of asymptomatic cases (Moyo et al, 2022) – support the notion of unrecognized transmitters in high-burden communities. And, while these results accommodate the potential for Mtb transmission to occur prior to the development of recognizable TB symptoms (Nguyen et al, 2023), they nevertheless rely on sputum production (itself a symptom of disease) for the detection of Mtb . This dependency on sputum production imposes a significant constraint on attempts to detect individuals with early TB, and is exacerbated by the difficulties encountered in obtaining useable samples from many individuals (Pai et al, 2023).…”
Section: Introductionmentioning
confidence: 90%
“…Through this lens, data from extensive community TB screening efforts utilizing sputum-GeneXpert – which have identified large numbers of asymptomatic cases (Moyo et al, 2022) – support the notion of unrecognized transmitters in high-burden communities. And, while these results accommodate the potential for Mtb transmission to occur prior to the development of recognizable TB symptoms (Nguyen et al, 2023), they nevertheless rely on sputum production (itself a symptom of disease) for the detection of Mtb . This dependency on sputum production imposes a significant constraint on attempts to detect individuals with early TB, and is exacerbated by the difficulties encountered in obtaining useable samples from many individuals (Pai et al, 2023).…”
Section: Introductionmentioning
confidence: 90%
“…There are no other estimates for the infectiousness of subclinical TB relative to clinical TB in the literature with which to compare our results. Using data from the 2007 Viet Nam prevalence survey, however, Nguyen et al, 2023 find that among children aged 6–10 years, those living with clinical, smear-positive TB, and those living with subclinical, smear-positive TB had similarly increased risks of TST positivity compared with those living without TB. Moreover, a recent small study from Uganda found no evidence of a difference in cumulative infection rates in household contacts of patients who did or did not report symptoms ( Baik et al, 2021 ).…”
Section: Discussionmentioning
confidence: 92%
“…This is expected since the latter group would likely be presenting at the later stages of the disease [ 1 ]. Data from prevalence and tuberculin surveys in Vietnam and mathematical models have further underscored the potential contribution of people with bacteriologically confirmed subclinical TB to M. tuberculosis transmission [ 9 , 83 , 84 ]. Considering the potential infectiousness of this population, relying on passive case finding [ 7 , 84 ] upon presentation at the health facilities or symptoms-based screening approaches could lead to further diagnostic delays, poorer prognosis and more severe post-TB sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…Data from representative TB prevalence surveys suggest that 50.4% of the prevalent bacteriologically confirmed TB in the general community was subclinical [ 5 ]. While only around half of the people with subclinical TB will progress to clinical TB [ 6 ], their potential ability to transmit the disease has serious implications for public health and the global efforts to end TB by 2035 [ 7 9 ]. Pathological changes occur while affected individuals remain at the subclinical stage [ 1 ], making it critical to identify and treat those at this disease phase.…”
Section: Introductionmentioning
confidence: 99%